Perbandingan Hasil Belajar Ekonomi Menggunakan Model Pembelajaran Kooperatif Tipe Student Teams Achievement Division (STAD) dengan Pembelajaran Konvensional Siswa Kelas X SMA Negeri 1 Pariaman - Masniari Masniari; Syamwil Syamwil (Universitas Negeri Padang, 2019)
This article to inform: difference learning outcomes using cooperative learning model type Student Teams Achievement Divisions with conventional at class XI SMA Negeri 1 Pariaman. The research used quasi ekseperimental design, technique is purpossive sampling, the instrument trials, gain score,validity, reliability, different test problem, and difficulty levels. Data collection by documentation and test result of learning outcome. The population in this study is XI SMA Negeri 1 Pariaman and sample is XI IPS 1 for class eksperiment and XI IPS 2 for class control. The analytical method used paired sample t-test and independent samplet-test analysis. The result is : there are differences in student learning outcomes using cooperative learning model type Student Teams Achievement Divisions and conventional economic subjects in class XI SMA Negeri 1 Pariaman based on calculation with Sig. value of 0,000. Keyword: model student teams achievement divisions, konvensional, learning outcomes